2011
DOI: 10.1090/conm/533/10508
|View full text |Cite
|
Sign up to set email alerts
|

Some problems and techniques in set-theoretic topology

Abstract: Abstract. I survey some problems and techniques that have interested me over the years, e.g. normality vs. collectionwise normality, reflection, preservation by forcing, forcing with Souslin trees, and Lindelöf problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(42 reference statements)
0
2
0
1
Order By: Relevance
“…We can then transfer a filter G which is Lv(κ, ω 1 ) generic over V to get a filter G * which is j(Lv(κ, ω 1 )) generic over M such that j(p) ∈ G * whenever p ∈ G. This allows us to extend j to an elementary embedding from V [G] to M [G * ]. For an example of this technique, see the proof of Theorem 4.16 in [18].…”
Section: Applications Of X/mmentioning
confidence: 99%
“…We can then transfer a filter G which is Lv(κ, ω 1 ) generic over V to get a filter G * which is j(Lv(κ, ω 1 )) generic over M such that j(p) ∈ G * whenever p ∈ G. This allows us to extend j to an elementary embedding from V [G] to M [G * ]. For an example of this technique, see the proof of Theorem 4.16 in [18].…”
Section: Applications Of X/mmentioning
confidence: 99%
“…We can also consider preservation of Lindelöf and D by other kinds of forcing. For example, it is known that a space is Lindelöf in a Cohen or random real extension if and only if it is in the ground model [12], [17], [35], and [39]. The situation for D is more complicated; in [5] it is shown that a Lindelöf space X becomes a D-space in an extension by more than |X| Cohen reals.…”
Section: Other Forcingsmentioning
confidence: 99%
“…Consolidados como ferramenta, não tardou para que os submodelos elementares passassem a ser tratados também como objeto de estudo. Segundo [1], o primeiro estudo sistemático da técnica em si foi feito em [3]. Lá, dado um espaço topológico X, τ em um submodelo elementar M , X M é o espaço X ∩ M munido da topologia τ M que tem como base a família { U ∩ M : U ∈ τ ∩ M }.…”
Section: Introductionunclassified